Production of “Melomel” from Cupuaçu (Theobroma grandiflorum) Using the Probiotic Yeast Saccharomyces cerevisiae var. boulardii - Karina Nascimento Pereira; Handray Fernandes de Souza; Amanda Cristina Dias de Oliveira; Marcela Aparecida Deziderio; Victor Dédalo Di Próspero Gonçalves; Marina Vieira de Carvalho; Eliana Setsuko Kamimura (Fermentation)
Mead is a fermented alcoholic beverage obtained by diluting honey in water and adding yeast. However, the addition of fruit to this beverage gives rise to melomel. In this study we are proposing an interesting novelty which consists of developing cupuaçu (Theobroma grandiflorum) melomel by fermenting Saccharomyces cerevisiae var. boulardii. The aim of this study was to develop cupuaçu (Theobroma grandiflorum) melomel produced by S. boulardii and to evaluate its physicochemical and microbiological characteristics after refrigerated storage at 4 °C. To do this, a central composite design (CCD) was employed, with two independent variables, i.e., the initial soluble solids content of the honey must (°Brix) and the concentration of the cupuaçu pulp (%). A standardized amount of 1 g/L of S. boulardii yeast was used at a temperature of 25 °C and a fermentation time of 30 days. Using the results of the central composite design (CCD), the best conditions for producing the beverage were defined according to the objectives of the study. Thus, the experimental comparison was carried out under the conditions of 25 °Brix of initial soluble solids in the honey must, 10% cupuaçu pulp, and 10 days of fermentation at 25 °C. The cupuaçu melomel exhibited a cell viability of the probiotic yeast S. boulardii above 107 log CFU/mL, with an alcohol content of 8.22% (v/v), a pH of 3.43, a total acidity of 54.8 of (mEq/L), and soluble solids of 12.42°Brix. In addition, the beverage was subjected to simulated gastric and intestinal juices in vitro to evaluate the survival of the microorganisms under these conditions, and a concentration of 106 log CFU/mL of S. boulardii was obtained. In this way, it was possible to produce a probiotic fermented alcoholic beverage made from honey and cupuaçu.